Pheng Cheah. What Is a World? On Postcolonial Literature as World Literature. Durham: Duke UP, 2016. - Gregory R. Jackson (Studies in 20th & 21st Century Literature, 2017)
Review of Pheng Cheah. What Is a World? On Postcolonial Literature as World Literature. Durham: Duke UP, 2016.
Keywords: Postcolonial; world literature